Sentencia o ciencia. Análisis de los circuitos de producción y difusión del conocimiento de quienes operan jurídicamente en la Provincia de San Juan - Lloveras Quiroga, Soledad (2023)
Much of the academic production in legal sciences is carried out by people dedicated to the practice of law or by those who perform functions in the Judiciary or other state agencies. The scientific debate is mainly guided by those who spend only part of their time in research. However, there are few investigations in Argentina that account for how these people produce knowledge considered scientific. This means not knowing academic, epistemological, and methodological training or the work philosophy of those who produce a large part of legal sciences research. The work's objective is to carry out an exploratory investigation in the province of San Juan that investigates this group of people. So as to achieve this we make use of a qualitative methodology and we rely on in-depth interviews. We use semi-structured and open questions to obtain a personal account and interpretation from the interviewees of their research practices. The analysis of the data obtained was carried out using ATRLAS.ti (QDA software) which allows operating with large amounts of data, being able to incorporate them and work sequentially, enhancing the investigation. We believe that, although the analysis focuses on one province, it is possible to draw conclusions about the way in which legal sciences develops on a larger scale. At the end of the article, the most conclusive finding indicates that much of the knowledge that circulates in the legal field is improperly considered research since they are more related to tasks involving the work of law operations or teaching than scientific research itself. -- This article is a modified and expanded version of the exhibition at the XI Sociology Conference of the UNLP, in the City of La Plata, held in December 2022